Itch Beyond the Skin—Mucosal Itch - Lesslar, Olivia J. Ly; Smith, Peter K. (Frontiers in Allergy, 2021)
Itch is a nociceptive sensation linked with reflexes and cognitive motor actions. Intertwined with this is evidence of several factors including stress, anxiety, worry and frustration contributing to the physiological processes involved in itch (1,2). We traditionally think of itch as a sensation of the skin. This review explores itching that occurs at mucosal sites and junctional dermal sites - focusing on specific itch patterns and discussing the pathophysiological mechanisms that underlie them. From an evolutionary point of view, these sites are the guardian tissues - and are rich in sensory nerves and inflammatory cells. We briefly overview the mechanisms by which itch may occur, how this may be amplified in specific tissue sites, the clinical patterns this causes and some unique treatments.